2017
DOI: 10.1016/j.yebeh.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiepileptic drugs among diverse older Americans on Part D Medicare

Abstract: Introduction Older minority groups are more likely to have poor AED adherence. We describe adherence to antiepileptic drugs (AEDs) among older Americans with epilepsy. Methods In retrospective analyses of 2008–2010 Medicare claims for a 5% random sample of beneficiaries augmented by minority representation, epilepsy cases in 2009 were those with ≥1 claim with ICD-9 345.x or ≥2 with 780.3x, and ≥1 AED. New onset cases had no such claims or AEDs in the year before the 2009 index event. We calculated the Propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 26 publications
0
24
1
3
Order By: Relevance
“…Moreover, because of our research question, our cohort over-represented minority groups compared to a random sample of Medicare beneficiaries meeting similar inclusion criteria. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because of our research question, our cohort over-represented minority groups compared to a random sample of Medicare beneficiaries meeting similar inclusion criteria. 38 …”
Section: Discussionmentioning
confidence: 99%
“…The PDC is the ratio of the number of days with at least one AED prescription over the total number of days from the first AED prescription to the end of the last refilled prescription or to the end of follow‐up (whichever comes first). About 32% of cases had a PDC < 80%; Care concordant with Quality Indicators for Epilepsy Treatment (QUIET) 15, that is, whether adjustments to AEDs were made following a seizure. Among beneficiaries with a seizure for which an emergency room (ER) visit occurred (n = 4132), 50% had AED changes and care concordant with QUIET 15; Care concordant with QUIET 6 for new cases, that is, starting AED treatment with monotherapy (>90%); Care concordant with QUIET 9 for new cases, that is, at least two non–enzyme‐inducing AEDs tried before starting enzyme‐inducing drugs (about 60%); and, Presence of drug interaction risk (care not concordant with QUIET 11) for new cases (about 25%) …”
Section: Methodsmentioning
confidence: 99%
“…Among older Americans with epilepsy, about 1.5% of older adults, minority groups may be at risk of high costs of care. Recent studies have found that African Americans, for example, have poor adherence to antiepileptic drugs (AEDs) and are more likely to have seizures resulting in emergency room visits . As shown in younger populations with epilepsy, these factors may lead to higher costs of care as well as poor health status .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher price of innovator AEDs may actually decrease adherence, although this has not been studied explicitly. Among elderly patients in the United States, those living in high‐poverty postal codes or in deductible drug benefit insurance phases were more likely to be nonadherent than those in more affluent areas or cost‐sharing insurance phases . In Sweden, higher income and lower copayment increased AED refill adherence …”
Section: Clinical Studiesmentioning
confidence: 99%